CD8+ T cell exhaustion in the tumor microenvironment of breast cancer - Xie, Hanghang; Xi, Xiaowei; Lei, Ting; Liu, Hongli; Xia, Zhijia (Frontiers in Immunology, 2024)
CD8+ T cells are crucial cytotoxic components of the tumor immune system. In chronic inflammation, they become low-responsive, a state known as T cell exhaustion (TEX). The aim of immune checkpoint blockade is to counteract TEX, yet its dynamics in breast cancer remain poorly understood. This review defines CD8+ TEX and outlines its features and underlying mechanisms. It also discusses the primary mechanisms of CD8+ TEX in breast cancer, covering inhibitory receptors, immunosuppressive cells, cytokines, transcriptomic and epigenetic alterations, metabolic reprogramming, and exosome pathways, offering insights into potential immunotherapy strategies for breast cancer.